Lake variables - Sonde profiling from Erken, Floating platform 2014-2017, 2016-05-31–2016-11-02 - Erken Laboratory (Uppsala University, 2022)
Manual or high frequency lake profiling using sonde technology over various water depths to measure lakes of SITES Water.
Erken Laboratory (2022). Lake variables - Sonde profiling from Erken, Floating platform 2014-2017, 2016-05-31–2016-11-02 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/whcdM-JHYdMzhouMfvPT2T7s
Keywords: Erken Laboratory; Chlorophyll concentration; Conductivity; Lake; Turbidity; Time instant; Time instant; Digital number of profile; Digital number of profile; Water depth; Water depth; Water temperature; Water temperature; Electrical conductivity; Electrical conductivity; Specific conductivity; Specific conductivity; pH; pH; Oxidation Reduction Potential; Oxidation Reduction Potential; Turbidity_FNU; Turbidity_FNU; Chlorophyll fluorescence; Chlorophyll fluorescence; Oxygen saturation; Oxygen saturation; Phycocyanin Fluorescence; Phycocyanin Fluorescence; Fluorescent dissolved organic matter; Fluorescent dissolved organic matter; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap